Identification of additional probiotic attributes in yeasts isolated from tarhana fermentation - Erdem, Belgin; Kaya, Halil Ibrahim; Tulumoglu, Sener; Coteli, Ebru; Simsek, Omer (SPRINGER, 2025)
Fermented foods constitute a valuable source of probiotics for both bacteria and yeasts. To date, however, there has been a limited amount of research conducted on Saccharomyces cerevisiae, Kazakhstania servazzi, Kluyveromyces marxianus and Torulaspora delbrueckii isolated from tarhana. The objective of the research is to identify additional probiotic characteristics other than the leavening activity exhibited by yeasts that were previously isolated from tarhana fermentation. In this study, yeasts were subjected to subsequent acid and bile salt tolerance, bile salt hydrolysis, antagonistic activity, aggregation activity (auto-aggregation and co-aggregation), cholesterol assimilation, folate production, biofilm production, and hemolysis activity. S. cerevisiae PCF122, S. cerevisiae PCF107, and S. cerevisiae PCF134 strains grew at pH 2 and 2,5 but remained at pH 3. Except for S. cerevisiae PCF115 and T. delbrueckii PCF150, all yeasts were found to be 0,5% and 1,0% oxalate tolerant. All yeasts hydrolyze oxalate (bile salt), but only S. cerevisiae PCF115 and T. delbrueckii PCF150 produced EPS. Yeasts also exhibited significant amounts of autoaggregation (46-87%). After 24 and 48 h incubation, all strains assimilated cholesterol at rates ranging from 10,4% to 87,5% and 10,6-91%, respectively. The highest folate production was determined at S. cerevisiae PCF108 (56 mu g/mL) and the lowest was at S. cerevisiae PCF110 and K. marxianus PFC120 (18 mu g/mL). In conclusion, yeasts that existed in tarhana fermentation showed cholesterol assimilation, folate production, and aggregation activity which are additional probiotic attributes that would have consumer health promotion, beside these yeast leaven the tarhana dough.
Keywords: Probiotic yeasts; S. cerevisiae; K. servazzi; K. marxianus; Cholesterol assimilation; FOLATE CONTENT; INFANT FECES; RAW-MILK; STRAINS; KLUYVEROMYCES; SACCHAROMYCES; CHOLESTEROL; DAIRY; ASSIMILATION; FOODS; Microbiology